THE EFFECT OF ISLAMIC FINANCIAL LITERACY, SPIRITUAL INTELLIGENCE, AND BUSINESS ETHICS ON THE BEHAVIOR OF THE MILLENNIAL GENERATION WITH THE MEDIATING VARIABLE OF INTENTION TO USE ISLAMIC BANKING SERVICES IN DEPOK CITY - Widhy Prasetyo; Mukhaer Pakkanna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT Sharia banking is growing rapidly, no less than conventional banks. The Sharia Banking industry illustrates an increase even though the movement is slow. This research aims to analyze the influence of Sharia Financial Literacy, spiritual intelligence, and business ethics on the Intention to Use Sharia Banking Services while testing the mediating role of the intention variable. This research is explanatory research with a quantitative approach. The population used in this research is the millennial generation, namely the generation born in 1981-1996 (currently aged 28-43 years) who have used or are presently using Sharia Banks in Depok City, with a sample of 157 people. The analysis method used is SEM-PLS. The research results show that Sharia Financial Literacy, Spiritual Intelligence, and Business Ethics have a positive effect on Intention to Use Sharia Banking Services. Intention to Use acts as a mediating variable on the influence of Financial Literacy, spiritual intelligence, and business ethics on Sharia Banking Use Behavior